Pressure-dependent semiconductor to semimetal and Lifshitz transitions in 2H-MoTe2: Raman and first-principles studies. (1st February 2017) - Bera, Achintya; Singh, Anjali; Muthu, D V S; Waghmare, U V; Sood, A K
Abstract: High pressure Raman spectroscopy of bulk 2H-MoTe2 up to  ̃29 GPa is shown to reveal two phase transitions (at  ̃6 and 16.5 GPa), which are analyzed using first-principles density functional theoretical calculations. The transition at 6 GPa is marked by changes in the pressure coefficients of A 1 g and E 2 g 1 Raman mode frequencies as well as in their relative intensity. Our calculations show that this is an isostructural semiconductor to a semimetal transition. The transition at  ̃16.5 GPa is identified with the changes in linewidths of the Raman modes as well as in the pressure coefficients of their frequencies. Our theoretical analysis clearly shows that the structure remains the same up to 30 GPa. However, the topology of the Fermi-surface evolves as a function of pressure, and abrupt appearance of electron and hole pockets at P ∼ 20 GPa marks a Lifshitz transition.